2014
DOI: 10.4103/0973-7847.134245
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of diabetes-mellitus-induced male reproductive dysfunctions in experimental animal models with medicinal plants

Abstract: Today diabetes mellitus has emerged as a major healthcare problem throughout the world. It has recently broken the age barrier and has been diagnosed in younger people also. Sustained hyperglycemia is associated with many complications including male reproductive dysfunctions and infertility. Numerous medicinal plants have been used for the management of the diabetes mellitus in various traditional system of medicine and in folklore worldwide as they are a rich source of bioactive phytoconstituents, which lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Functional outcome of the morphological improvement by LBP in the male mice subjected to STZ was further studied. It is well known that long-term hyperglycemia can cause loss of libido and low quality sperm [42][43][44]. In animal studies, it has also been demonstrated that the ML and IL extended with decreased MF, IF and increased PEI and EL in diabetic animals.…”
Section: Discussionmentioning
confidence: 84%
“…Functional outcome of the morphological improvement by LBP in the male mice subjected to STZ was further studied. It is well known that long-term hyperglycemia can cause loss of libido and low quality sperm [42][43][44]. In animal studies, it has also been demonstrated that the ML and IL extended with decreased MF, IF and increased PEI and EL in diabetic animals.…”
Section: Discussionmentioning
confidence: 84%
“…Diabetes mellitus (DM) is a chronic metabolic disease. It is rapidly emerging as a major public health problem that demands special attention in term of its management (Jain & Jangir, ; Jangir and Jain, ). The number of diabetic patients is rapidly increasing each year especially in developing countries due to the lifestyle and dietary habits.…”
Section: Introductionmentioning
confidence: 99%
“…The DM is characterized by a sudden and distinct loss in body weight, a symptom as also observed herein. The decreases in body and testis weights of DM rats showed the damage or destruction of structural proteins related to diabetes [3] . When diabetic rats were treated with the MLT, a weight loss in the body was reversed.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it may lead to a decrease in libido and fertility, thus people's quality of life and life expectancy could become inevitablely reduced [3] . AKMAN, ŞENGÜL, ÖZKANLAR, CAN KOÇ, KARADENİZ, ŞİMŞEK The well-known effect of alloxan, used herein as diabetic agent, on the β-cells in pancreas is to cause the development of insufficient synthesis of insulin and, thus, increasing the blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation